Pengaruh Model Pembelajaran Berbasis Masalah (Problem Based Learning) Terhadap Hasil Belajar Materi Gaya pada Siswa Kelas IV SDN Manunggal - Aris Setiawan; Parrisca Indra Perdana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was motivated by low student learning outcomes. Not only that, students have not been able to analyze and understand problems because interaction is still low and students are not actively involved in learning which results in the concept delivery process not being conveyed optimally. This is due to the application of learning models that are less effective in improving learning outcomes. The aim of this research is to determine the effect of the problem-based learning model on student learning outcomes in style material in class IV of SD Negeri Manunggal, Jombang Regency. This type of research is quantitative research with an experimental method. The design used is Pre Experimental with One Group Pre Test – Post Test Design. The population and sample used in this research were all fourth grade students at SD Negeri Manunggal with a total of 24 students. The sampling technique uses saturated samples. Data collection techniques use observation and critical thinking ability tests. The results of the paired sample t test obtained a sig value. Of 0,000. Based on the test criteria if the sig value. (2 – tailed ) < 0.05 (0.000 < 0.05) then H0 is rejected and Ha is accepted. And if Tcount is greater than Ttable then H0 is rejected and Ha is rejected. The tcount obtained was 9.105 > 2.069, so H0 was rejected and Ha was accepted, so it can be concluded that in this research there is an influence of the problem-based learning model on student outcomes.